2016
DOI: 10.1158/1078-0432.ccr-15-1666
|View full text |Cite
|
Sign up to set email alerts
|

The Bromodomain Inhibitor JQ1 and the Histone Deacetylase Inhibitor Panobinostat Synergistically Reduce N-Myc Expression and Induce Anticancer Effects

Abstract: Purpose: Patients with neuroblastoma associated with MYCN oncogene amplification experience a very poor prognosis. BET bromodomain inhibitors are among the most promising novel anticancer agents as they block BRD3 and BRD4 from activating oncogene transcription. However, treatment with BET bromodomain inhibitors alone does not result in cancer remission in many murine models.Experimental Design: MYCN-amplified neuroblastoma cells were treated with vehicle control, the BET bromodomain inhibitor JQ1, the histone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 22 publications
5
93
0
Order By: Relevance
“…As for mechanism of the suppression of BRD4 by JQ1, it is generally agreed that JQ1 competitively bind to acetyl-lysine recognition pockets, displace BRD4 from chromatin, and reduce the expression of oncogenes, leading to cancer cell growth inhibition and apoptosis [47]. Consistent with this statement, Fiskus et al [13] showed that treatment with JQ1 reduced the BRD4 occupancy at the promoters of c-myc, BCL-2, and CDK6 and attenuated the mRNA and protein expression of these associated genes in acute myelogenous leukemia (AML) blast progenitor cells (BPC).…”
Section: Discussionmentioning
confidence: 99%
“…As for mechanism of the suppression of BRD4 by JQ1, it is generally agreed that JQ1 competitively bind to acetyl-lysine recognition pockets, displace BRD4 from chromatin, and reduce the expression of oncogenes, leading to cancer cell growth inhibition and apoptosis [47]. Consistent with this statement, Fiskus et al [13] showed that treatment with JQ1 reduced the BRD4 occupancy at the promoters of c-myc, BCL-2, and CDK6 and attenuated the mRNA and protein expression of these associated genes in acute myelogenous leukemia (AML) blast progenitor cells (BPC).…”
Section: Discussionmentioning
confidence: 99%
“…This transcriptional effect likely contributes to the requirement for pre-treatment with panobinostat, for optimal combinatorial effects with olaparib, and thus, has important implications for clinical development of this combination. The potential to harness transcriptional reprogramming as a therapeutic anti-cancer strategy is emphasized by studies showing enhanced anti-tumor effects of HDACi combined with various chromatin-modulating drugs, including DNA methyltransferase and bromodomain inhibitors [34, 35]. Finally, it is possible that lower doses of panobinostat administered with therapeutic doses of olaparib will have significant benefit with minimal added toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Sengupta et al 2015; S. Sengupta et al 2015; Shahbazi et al 2016; Zhang et al 2016; Bid et al 2016), a key activator of RNAPII transcription at active chromatin marks (Jang et al 2005; LeRoy et al 2008; Rahman et al 2011). An alternative target is CDK7, a member of the cyclin-dependent kinase family involved in regulation of RNAPII phosphorylation, controlling transcriptional initiation, pausing, and elongation (Fisher & Morgan 1994; Glover-Cutter et al 2009; Larochelle et al 2007; Larochelle et al 2012; Rossignol et al 1997; Serizawa et al 1995).…”
Section: Introductionmentioning
confidence: 99%